Strategi Bauran Pemasaran untuk Meningkatkan Volume Penjualan Ikan Hias (Ornamental Fish) pada PT Agung Aquatic Marine, Denpasar Bali - Anugrah Anugrah; Budiman Budiman; Karma Karma (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to find out the marketing mix strategy for ornamental fish to increase sales volume at PT Agung Aquatic Marine, Denpasar Bali. This research uses descriptive qualitative research and also uses SWOT analysis (Strength, Weakness, Opportunity, Threat). SWOT analysis is an analysis used to evaluate opportunities and threats in the external environment as well as the strengths and weaknesses of the company's internal environment. The results of this research show that an IFAS score of 2.87 indicates a strong internal position, an EFAS score of 2.59 shows that the company responds to existing opportunities in a good way and avoids threats in its industrial market. The Cartesian diagram shows the company's position in an aggressive state, which is very profitable for the company. The marketing strategy used by the company to increase sales is that the company maintains and utilizes quality and varied products so that market segmentation becomes wider or increases, maintains consumer trust by being consistent in the performance provided and actively communicating to create mutually beneficial agreements.